EXISTENTIAL CRISIS IN BARBIE FILM (2023) - Lulu Aprilia; Dina Amelia (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2026)
This study analyzes the existential crisis experienced by the main character in the film Barbie (2023) using Jacques Lacan's psychoanalytic theory (Imaginary Order, Symbolic Order, and The Real) combined with Viktor Frankl's existential psychology. The results of the analysis show that Barbie's identity was initially formed in the Imaginary Order, namely through the ideal image of perfection determined by popular culture. Upon entering the Symbolic Order, Barbie was confronted with patriarchal social norms and external labels that shook her concept of self. In the next stage, she encounters The Real in the form of anxiety, physical changes, and awareness of death and reality that cannot be symbolized or hidden by fantasy. This encounter gives rise to an existential void, a condition devoid of meaning, which drives Barbie to seek an authentic identity and purpose in life beyond the standards of false perfection. By combining Lacanian psychoanalysis and Frankl's logotherapy, this study shows that Barbie's existential crisis is not only a personal conflict, but also a reflection of broader cultural anxieties about femininity, freedom, and authenticity in contemporary society